(untitled) - Zakir Ullah, Ahmad Ullah, Naqib Ur Rehman, Zohaib Zahir (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
This study covers the elements of Orientalism, in the character of Kim, in the novel, Kim. Kim, the major character, is focused who exhibits both as an Occident and an Orient. Some events show the features that Kim learns from them and the characteristics that he installs in Orientals. Kim depicts the land of the subcontinent, a hard abode for everyone. This study applies Orientalist approach on two levels: impressionism and expressionism. Here, impressionism is the impression that the West has about the East. Expressionism, likely, is the performing of many inhumane and senseless actions that an Oriental is thought to be having. In this way, the major character of this novel, Kim, is depicted as devoid of any good and socially acceptable habits. Orientalists are considered to be devoid of any positive trait. So, the very concept of Orientalism is a danger to humanity in the mind of the West. This study focuses on the many black deeds that are associated with the East whether those bad habits are present there or not. It proves the allegations false against the East and shows to the readers that good and bad are part of every human society and the West is not a standard for the East.